The Application of the Approach of “Cognitive Structure” in the Teaching Methods of the Holy Quran in Respect to Meaningful Learning - Zahra Safian Jozdani; Reza Saadat Nia (آموزه‌های قرآنی, 2021)
The present research with paying attention to the importance and impact of the stability of the cognitive structure in the area of the teaching fields has been organized. The way which is the persons have codified the information and knowledge in their minds is “cognitive structure”. One of the important results in the way of the establishment and stability of cognitive structure is to provide meaning for learning means correlation of the new knowledge with concepts which are in a person’s cognitive structure before. Whatever these connections are more the perception is deeper. According to the verse 9 of the surah al-Isra ﴿إنَّ هَذَا الْقُرْآنَ یَهْدِی لِلَّتِی هِیَ أَقْوَمُ...﴾ (Surely this Quran guidance to what is most upright…). It is believed that with relation to its teaching responsibility and upright guidance the holy Quran defines its method. With considering the holy Quran and the text of education with analytic-descriptive method this note is going to extract the methods that the Quran has applied for this aim while explaining the special position of the cognitive structure and its soundness in the process of teaching. The findings show that the establishment and the soundness of the cognitive structure in the holy Quran has strategies containing: the expression of the issue in the area of time events, laying the ground work during speaking with, laying the ground work through stories, creating multi aspects for direct speaking with addresses, making constant connection of the speech with the prominent pillars of the pervious speeches and entering the emotional factor (such as imaging and composing the repetitions) to the frame of the cognitive structure pyramid.